Lettres sur la danse et sur les ballets de Jean-Georges Noverre : un plaidoyer pour la « recherche-création » au XVIIIe siècle ? - Lapeyre, Chantal (RACAR : Revue d'art canadienne / Canadian Art Review, 2023)
In Les Lettres sur la danse, first published in 1760, then in 1803–1804, and again in 1807, Jean-Georges Noverre developed four complementary aspects that could be said to inscribe this choreographer's approach within the dynamics of research-creation as they are known and debated today. First, Noverre undertakes a reflexive return to his long practice as a dancer, choreographer, and pedagogue. Redefining dance, Noverre then asserts its place among the other arts (which it struggles to impress) and thereby develops an original argument. Les Lettres subsequently deliver reflections on the act of creation itself, in which Noverre asserts the preeminent place of knowledge. Finally, Les Lettres attest to the desire for sharing and reciprocity that underscore the epistolary format itself.